FYVE1 Is Essential for Vacuole Biogenesis and Intracellular Trafficking in Arabidopsis. Issue 4 (19th February 2015) - Kolb, Cornelia; Nagel, Marie-Kristin; Kalinowska, Kamila; Hagmann, Jörg; Ichikawa, Mie; Anzenberger, Franziska; Alkofer, Angela; Sato, Masa H.; Braun, Pascal; Isono, Erika
Abstract : A phospholipid-binding protein regulates intracellular trafficking and vacuole formation. Abstract: The plant vacuole is a central organelle that is involved in various biological processes throughout the plant life cycle. Elucidating the mechanism of vacuole biogenesis and maintenance is thus the basis for our understanding of these processes. Proper formation of the vacuole has been shown to depend on the intracellular membrane trafficking pathway. Although several mutants with altered vacuole morphology have been characterized in the past, the molecular basis for plant vacuole biogenesis has yet to be fully elucidated. With the aim to identify key factors that are essential for vacuole biogenesis, we performed a forward genetics screen in Arabidopsis ( Arabidopsis thaliana ) and isolated mutants with altered vacuole morphology. The vacuolar fusion defective1 ( vfd1 ) mutant shows seedling lethality and defects in central vacuole formation. VFD1 encodes a Fab1, YOTB, Vac1, and EEA1 (FYVE) domain-containing protein, FYVE1, that has been implicated in intracellular trafficking. FYVE1 localizes on late endosomes and interacts with Src homology-3 domain-containing proteins. Mutants of FYVE1 are defective in ubiquitin-mediated protein degradation, vacuolar transport, and autophagy. Altogether, our results show that FYVE1 is essential for plant growth and development and place FYVE1 as a key regulator of intracellular trafficking and vacuole biogenesis.